METHODOLOGICAL ASPECT OF HUMAN CAPITAL ASSESMENT (Scientific electronic journal "Labor Economics and Human Capital", 2023)
The development trend of the world economy shows that one of the important factors of development is the knowledge, skills, abilities, ability and need to continue their education. In developed economies, the share of human capital in national wealth is up to 80%. In this regard, special attention is paid to the development of human capital in the developed countries of the world. In the process of building a New Uzbekistan, special attention is paid to issues such as economic growth, employment and quality of life, development of human capital. Economic growth is directly related to employment and health, quality of life, the level and quality of development and competitiveness of the education system. In particular, the human capital currently formed in Uzbekistan does not fully meet the needs of the economy for highly qualified personnel. Therefore, in the context of the development of innovative economies and digital technologies, it is expedient to improve the methodology of calculating human capital and the mechanisms that encourage its growth. Taking into account the world experience, this article proposes a methodology for identifying and evaluating key indicators of human capital at different levels as an important factor in the development of the national economy.
Keywords: human capital, human capital index, expected years of school.